Research of the characteristics of acoustic processes using wavelet transformation for detecting a diagnostic sign of the technical state of gas pumping units - Zamikhovskyі, Leonid; Zamikhovska, Olena; Pavlyk, Volodymyr (Technology audit and production reserves, 2021)
The object of research is the degradation processes that take place in gas-pumping units (GPU) during its long-term operation and lead to the appearance of defects and, as a result, to a change in its technical state. Today, methods of parametric and vibration diagnostics are used to determine the technical condition of the GPU. To identify diagnostic signs of the technical state of the GPU, various transformations are used, in particular the wavelet transforms used in vibration processing that accompany the operation of the GPU and their technological parameters. At the same time, in the study of the diagnostic signs of the technical state of the GPU, the acoustic processes accompanying the operation of the GPU, which can be more informative in comparison with the vibration ones, were practically not considered. The developed experimental research methodology and their technical support made it possible to record the acoustic processes accompanying the operation of the gas compressor unit type GTK-25-i of the Nuovo Pignon company (Italy). In the course of the experimental studies, the realizations of the acoustic processes of the GPU were obtained for its three states – «nominal», «defective» and «current». Further studies of acoustic processes for three states of the GPU type GTK-25-i and using the wavelet transform showed that by the appearance of the wavelet spectrograms it is difficult to notice the difference in the appearance or disappearance of various frequency components depending on the technical state of the GPU. To obtain quantitative indicators of this dependence, a discrete wavelet transform was carried out, which makes it possible to identify characteristic trends in the change in noise values at different scales. The values of the approximation norm and the detail norms in relation to the signal norm (in percent) were obtained for a five-level wavelet decomposition with datasets. A linear dependence of the norm of the wavelet-component of the fifth-order detailing on the operating time of GPU type GTK-25-i and (changes in the technical state), which can be taken as a diagnostic sign of its technical state, has been established. The investigated diagnostic feature can be used as the basis for the method of diagnosing the technical state of GPU type GTK-25-i based on the characteristics of its acoustic process using the wavelet transform. An approach to identifying a diagnostic sign of the technical state of a GPU type GTK-25-i is considered based on the characteristics of acoustic processes using a wavelet transform can be used to identify a diagnostic sign of a condition for any type of GPU.